2018
DOI: 10.1093/jas/sky223
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: Effect of machine, anatomical location, and replication on instrumental color of boneless pork loins

Abstract: The objective was to determine the effect of machine, anatomical location, and replication (multiple readings) on instrumental color and to characterize the amount of variation each factor contributed to overall color. Instrumental color was measured three times on the anterior and three times on the posterior end of 250 pork loins with two different Minolta CR-400 Chroma meter devices. Each Minolta was programed to use a D65 illuminant, 2° observer with an 8 mm aperture, and calibrated with white tiles specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This is noteworthy as HunterLab spectrophotometers are the second most commonly used instruments for the determination of colour in meat studies (Tapp et al 2011). Methods can impact on colour data precision and reproducibility, as Barkley et al (2018) reported when pork loin colour values were shown to change as the repeat measures (readings) increased from one to three. This example demonstrates the importance of reporting the number of repeat measures when assessment meat colour to ensure the reader's comprehension when interpreting the results.…”
Section: Introductionmentioning
confidence: 97%
“…This is noteworthy as HunterLab spectrophotometers are the second most commonly used instruments for the determination of colour in meat studies (Tapp et al 2011). Methods can impact on colour data precision and reproducibility, as Barkley et al (2018) reported when pork loin colour values were shown to change as the repeat measures (readings) increased from one to three. This example demonstrates the importance of reporting the number of repeat measures when assessment meat colour to ensure the reader's comprehension when interpreting the results.…”
Section: Introductionmentioning
confidence: 97%
“…These findings were expected, because color values were different between machines when different operational settings were used in a previous study (Brewer et al, 2001). Additionally, Barkley et al (2018) determined that means differ between machines even when operational settings remained constant. However, both of the previous studies only investigated differences in mean values, and not variability of those readings.…”
Section: Discussionmentioning
confidence: 69%
“…To maximize replicability of instrumental color measurements, it is important to have an understanding of which variables may impact instrumental variability. Barkley et al (2018) conducted a study analyzing the effect of the machine itself on instrumental color measurements when all settings were kept constant and when loins were measured in a controlled environment. While statistical differences in color traits between machines were present, the study concluded that said differences were too small to be of practical importance and that those machines could be used interchangeably as long as each machine used identical settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations